Optimizing The Role Of Greenpeace In The Citarum River Conservation Program, West Java - Imam Budiman; Tine Ratna Poerwantika; Ika Sri Hastuti (Sean Institute, 2023)
The river is a source of clean water for the survival of living things. Unfortunately, this source of life is not well guarded. Indonesia has rivers that irrigate the mainland and are divided into main rivers and tributaries. The Citarum River is one of the longest main rivers in the Java region, originating in Cisanti, the slopes of Mount Wayang, one of the children of Mount Malabar, in the South Bandung area and empties into the Java Sea. Therefore the Citarum river has a lot of potential for harmony in the lives of many people. In fact, the condition of the Citarum river is very worrying with the many environmental pollution violations committed by irresponsible people. This research was conducted using the qualitative analysis content method based on secondary data to describe and analyze the concept of environment and development. Data collection was carried out by means of literature studies and interviews. The paper aims to analyze the role played by Greenpeace in reducing violations of environmental pollution and rehabilitating the Citarum river basin (DAS). In general, Greenpeace carries out its role as a world organization that cares about environmental issues by carrying out the rule application and socialization functions which are expected to reduce toxic waste in the Citarum river basin. The expected outputs of this research are scientific journals and intellectual property rights as a form of the results of this research so that they are more useful for science, especially in the field of NGOs and the environment.